Extreme enhanced myometrial vascularity following cesarean scar pregnancy: a new diagnostic entity. (12th December 2022) - Timor-Tritsch, Ilan E.; McDermott, W. Meredith; Monteagudo, Ana; Calί, Giuseppe; Kreines, Fabiana; Hernandez, Sasha; Stephenson, Courtney; Bryk, Hillel; D'Antonio, Francesco
Abstract: Objective: To define, illustrate and to follow-up the diagnosis, pathophysiology and treatment of a subset of the known enhanced myometrial vascularity (EMV): its extreme form, associated with cesarean scar pregnancies (CSP) and with some cases pf placenta accreta spectrum being at increased risk of significant bleeding complications. We also aim to provide guidance to the management of such cases. Material and methods: This is an IRB-approved retrospective observational study of thirteen patients with an extreme form of EMV complicating CSPs. Patient's age, parity, number of cesarean deliveries, initial and time to negative serum hCG levels, primary and secondary diagnoses, blood flow peak systolic velocities, primary and secondary treatments, uterine artery embolization and outcomes were recorded. Results: Gestational ages ranged 6–11 weeks at initial presentation. Initial serum hCG was 20.0–102.48 mIU/L (mean 44.4 mIU/L). Diameter of EMV reached 20–75 mm (mean 46.8 mm). The mean peak systolic velocity (PSV) was 84.2 cm/s (range 46.7–118.0). Primary treatments were: systemic methotrexate (MTX) alone; D&C alone; MTX and D&C; local and systemic intra-gestational MTX injection; double cervical ripening balloon with systemic MTX; misoprostol and D&C; emergent UAE. UAE and hysterectomy were the two main secondary treatments in 10 women except 1 having a D&C after UAE, and in 1 the lesion regressed without secondary treatment. Mean time to nonpregnant hCG levels was 21–122 days (mean 67.2). Mean follow-up was 110.2 days (range 26–160). Ten women were treated with UAE, 6 had one, 3 had two embolizations. Two women had hysterectomies, one of these for persistent bleeding. Based upon the common denominators of the clinical and the US pictures, our definition of extreme EMV is sustained form of EMV associated with treated or untreated CSP, with peak systolic velocities of blood flow over 50 cm/s, slow return or plateauing serum hCG, with or without clinically significant vaginal bleeding, unresponsive to initial or secondary treatment requiring uterine artery embolization or hysterectomy. Conclusion: The EMV developing in the background of retained placental tissue associated with CSP differs following the normal regression of the physiologically re-modelled, dilated vascular bed from the faulty "disrepair" of the vessel wall in in treated or untreated CSPs. The "threatening" appearance of the above EMVs warranted the term "extreme", creating their separate new sub-category." Extreme forms of CSP-related EMV pose significant diagnostic and management challenges. Prompt recognition and intervention, the proactive use of UAE, can maximize the outcome of women affected by this "extreme" form of EMV enabling to preserve reproductive potential. Obstetricians, gynecologists and interventional radiologists should be aware of this form of severe vascular complication.